THE IMPACT OF GREEN ACCOUNTING IMPLEMENTATION AND ENVIRONMENTAL PERFORMANCE ON PROFITABILITY IN FOOD AND BEVERAGE SECTOR MANUFACTURING COMPANIES LISTED ON THE STOCK EXCHANGE INDONESIA (BEI) IN 2019 - 2023 - Anju Dayantisyah; Thezar Fiqih Hidayat Hasibuan; Devi Ayu Putri Sirait (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This research aims to determine the effect of implementing Green Accounting, environmental performance on the profitability of manufacturing companies in the food and beverage sector listed on the Indonesia Stock Exchange in 2019 - 2023. This research uses secondary data, this secondary data was obtained from financial report data of manufacturing companies in the food and beverage sector and drinks listed on the Indonesia Stock Exchange (BEI) via www.idx.co.id or the websites of each company. The population in this study were food and beverage sector manufacturing companies listed on the Indonesian Stock Exchange, namely 42 food and beverage sector manufacturing companies. Purposive sampling technique was used to take samples in this research. The sample for this research are companies that meet the criteria, namely 8 manufacturing companies in the food and beverage sector. The data analysis technique in this research uses SPSS. The results of this research show that Green Accounting has a positive and significant effect on profitability, and environmental performance has a positive and significant effect on profitability. Meanwhile, simultaneously it shows that Green Accounting and environmental performance have a significant positive effect on profitability.